A Glimpse of Industrialization in Nepal: Reality and Challenges - Chandra Prasad Dhakal (Interdisciplinary Journal of Management and Social Sciences, 2022)
Nepal is land locked nation with concise number of population and difficult geographical structure. Industrialization is one of the major challenges of Nepal for Economic development. In this study, it analyzes major challenges of industrialization in Nepal in term of economic prosperity and development. The study followed qualitative research design and only used secondary source of data that were collected through different libraries and internet. Conclusion of this study is based on the analysis and interpretation of data collected from the different sources. Access on global market, lack of infrastructure for industries, political instability, lack of capital and skilled manpower, lack of the access on sea transportation and weak road network, lack of raw materials are the major challenges of industrialization in Nepal.